Spatial-temporal variation of parasites in Cnemidophorus ocellifer (Teiidae) and Tropidurus hispidus and Tropidurus semitaeniatus (Tropiduridae) from Caatinga areas in northeastern Brazil - Brito, Samuel V.; Ferreira, Felipe S.; Ribeiro, Samuel C.; Anjos, Luciano A. [UNESP]; Almeida, Waltecio O.; Mesquita, Daniel O.; Vasconcellos, Alexandre (Springer, 2014)
Parasites are natural regulators of their host populations. Despite this, little is known about variations in parasite composition (spatially or temporally) in environments subjected to water-related periodic stress such as the arid and semiarid regions. The objective of this study was to evaluate the spatial-temporal variation in endoparasite species' abundance and richness in populations of Neotropical Cnemidophorus ocellifer, Tropidurus hispidus, and Tropidurus semitaeniatus lizards in the semiarid northeast of Brazil. The location influenced the abundance of parasites in all analyzed lizard species, while season (dry and rainy) only influenced the total abundance for T. hispidus. In all seasons, males significantly showed more endoparasites than females in all lizard species, although for T. hispidus, this difference was only found in the dry season. Seasonal variations affect the abundance patterns of parasites. Likely, variables include environmental variations such as humidity and temperature, which influence the development of endoparasite eggs when outside of the host. Further, the activity of the intermediate hosts and the parasites of heteroxenous life cycles could be affected by an environmental condition. The variation in the abundance of parasites between the sampling areas could be a reflection of variations in climate and physiochemical conditions. Also, it could be due to differences in the quality of the environment in which each host population lives.